1992
DOI: 10.1139/y92-044
|View full text |Cite
|
Sign up to set email alerts
|

ATP-MgCl2 restores renal microcirculation following trauma and severe hemorrhage

Abstract: Although ATP-MgCl2 enhances the recovery of renal function after ischemia and reperfusion, it is not known whether this agent has any beneficial effects on renal microcirculation and function in a nonheparinized model of trauma and severe hemorrhage. To study this, a midline laparotomy was performed (i.e., trauma induced) and the rats were bled to and maintained at a mean arterial pressure of 40 mmHg (1 mmHg = 133.32 Pa) until 40% of the maximum shed blood volume was returned in the form of Ringer's lactate (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Adenosine uptake mediates recovery of ATP content in postischemic cultured renal tubular cells (Cadnapaphornchai et al, 1991). Enhanced recovery from acute renal failure in rats by postischemic infusion of ATP-MgCl 2 was described earlier (Osias et al, 1977;Glazier et al, 1978;Siegel et al, 1980;Gaudio et al, 1982;Hirasawa et al, 1983;Sumpio et al, 1984;Wang et al, 1992bWang et al, , 1992dMartin et al, 1992). Renal injury can arise as a consequence of ischemia and reperfusion during renal transplant surgery.…”
Section: Ischemiamentioning
confidence: 73%
“…Adenosine uptake mediates recovery of ATP content in postischemic cultured renal tubular cells (Cadnapaphornchai et al, 1991). Enhanced recovery from acute renal failure in rats by postischemic infusion of ATP-MgCl 2 was described earlier (Osias et al, 1977;Glazier et al, 1978;Siegel et al, 1980;Gaudio et al, 1982;Hirasawa et al, 1983;Sumpio et al, 1984;Wang et al, 1992bWang et al, , 1992dMartin et al, 1992). Renal injury can arise as a consequence of ischemia and reperfusion during renal transplant surgery.…”
Section: Ischemiamentioning
confidence: 73%
“…5,[8][9][10] Similarly, our previous studies have shown that administration of pentoxifylline or adenosine triphosphate-magnesium chloride after trauma-hemorrhage and resuscitation significantly improves endothelial function and has many other beneficial effects on experimental animals. 1,3,[28][29][30][31][32][33][34][35][36][37][38][39] The precise mechanism responsible for the beneficial effects of flutamide on endothelial function remains unknown. Previous studies have shown that plasma testosterone levels are not significantly altered after traumahemorrhage and resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previously described nonheparinized model of trauma-hemorrhage in the rat was used with minor modifications (28). Briefly, rats were fasted overnight before the experiment but allowed water ad libitum.…”
Section: Methodsmentioning
confidence: 99%